FIRST AID IN CHILDREN WHEN THE RESPIRATORY TRACT IS CLOGGED WITH YOTJISM - Toxirova R.I, Yunusova Z.V (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
this article will talk about a very common situation in the life of young children. That is, the clogging of foreign bodies in the airways and how to remove it. Depending on the age of the children, they will be given the first ambulance and will be told about the need to choose toys that are suitable for their age.